Call to increase statistical collaboration in sports science, sport and exercise medicine and sports physiotherapy - Sainani, K. L.; Borg, D. N.; Caldwell, A. R.; Butson, M. L.; Tenan, M. S.; Vickers, A. J.; Vigotsky, A. D.; Warmenhoven, J.; Nguyen, R.; Lohse, K. R.; Knight, E. J.; Bargary, N. (British Journal of Sports Medicine, 2021)
Statistical and methods errors are common in sports science and sports medicine/physiotherapy research. Collaboration between researchers and statisticians can reduce errors. Only about 13% of papers published in quartile one sports science journals include a coauthor affiliated with a statistics or other methods-oriented department. We identify barriers to collaboration: a lack of appreciation of the importance of statistical expertise by scientists, lack of understanding of the value of sport and exercise research among statisticians, lack of resources to hire statisticians, a dearth of statisticians available to collaborate, and communication and cultural barriers among fields. We recommend that sports science and medicine programmes increase formal and informal interactions with statisticians and expand their statistical curricula; we also call for the development of a quantitative specialisation within the field.